Harnessing Artificial Intelligence to Enhance Personalized Learning in Educational Environments - Zing, Kyaew; Min, Aung; Soe, Thura; Thet, Mya (Educia Journal, 2023)
This study explores the integration of artificial intelligence (AI) in personalized learning environments, focusing on its impact on learner engagement, motivation, equity in education, and the ethical concerns surrounding its adoption. Using a qualitative case study approach, data were gathered through semi-structured interviews, focus group discussions, and document analysis from three educational institutions that implemented AI-driven personalized learning platforms. The findings reveal that AI enhances learner engagement by providing tailored learning experiences, fostering intrinsic motivation, and promoting autonomy. However, challenges related to equity emerged, particularly concerning access to technology and the potential for widening educational disparities. Ethical concerns, such as algorithmic bias and privacy issues, were also highlighted, emphasizing the need for careful consideration when adopting AI systems in education. Teachers and administrators expressed a mixed perception, with some viewing AI as a transformative tool for individualized instruction, while others raised concerns about its potential to replace traditional teaching methods. This study contributes to the growing body of literature on AI in education by addressing gaps related to its practical application, ethical implications, and the varying perceptions of stakeholders. The findings suggest that while AI offers significant potential for personalized learning, its implementation must be approached cautiously, ensuring equitable access and ethical safeguards.